Christians gather at the high altar to touch the crucifixion - Mumbai Archive Project Team (Jio Institute, 2024)
Christians gather at the high altar to touch the crucifixion, particularly the Five Holy Wounds. In Catholic tradition, these wounds refer to the five penetrating wounds that Jesus Christ received during his crucifixion. In the background is the coat of arms of Cardinal Oswald Gracias, Archbishop of Bombay, with the phrase ‘To Reconcile All Things in Christ’ appearing on top.